2016
DOI: 10.1038/srep39036
|View full text |Cite
|
Sign up to set email alerts
|

Genes essential for the morphogenesis of the Shiga toxin 2-transducing phage from Escherichia coli O157:H7

Abstract: Shiga toxin 2 (Stx2), one of the most important virulence factors of enterohaemorrhagic Escherichia coli (EHEC), is encoded by phages. These phages (Stx2 phages) are often called lambda-like. However, most Stx2 phages are short-tailed, thus belonging to the family Podoviridae, and the functions of many genes, especially those in the late region, are unknown. In this study, we performed a systematic genetic and morphological analysis of genes with unknown functions in Sp5, the Stx2 phage from EHEC O157:H7 strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…TEM classified the stx2a -convering phage of E. coli O104:H4 as short-tailed (Beutin et al, 2012 ). Secondly, Mondal et al ( 2016 ) identified nine genes responsible for phage morphogenesis of short-tailed phage designated SP5, and these were found by BLAST to be nearly identical (>99%) on amino acid level to the homologs from phage PA2. Notably, one of these genes, ECs1228, is predicted to encode a phage tail fiber and 100% identical to the PA2 phage homolog on amino acid level.…”
Section: Discussionmentioning
confidence: 99%
“…TEM classified the stx2a -convering phage of E. coli O104:H4 as short-tailed (Beutin et al, 2012 ). Secondly, Mondal et al ( 2016 ) identified nine genes responsible for phage morphogenesis of short-tailed phage designated SP5, and these were found by BLAST to be nearly identical (>99%) on amino acid level to the homologs from phage PA2. Notably, one of these genes, ECs1228, is predicted to encode a phage tail fiber and 100% identical to the PA2 phage homolog on amino acid level.…”
Section: Discussionmentioning
confidence: 99%
“…The location of the host integration site and genome size for each prophage is indicated in parentheses after the phage name. Open reading frames of prophages λ, 933W, and Sp5 [28, 91, 92] are shown in comparison to those of prophage 1720a-02, and are depicted as arrows pointing in the direction of transcription. The site of insertion of the chloramphenicol cassette ( cat ) in phage 1720a-02 is indicated with an open triangle.…”
Section: Supporting Informationmentioning
confidence: 99%
“…The main virulence factors of STEC are the phage-encoded cytotoxins called Shiga toxins (Stx family), with several toxin subtypes [3]. Stx phages can be present, either integrated in the STEC chromosome as temperate bacteriophage or as free particles in the environment [4][5][6]. STEC strains are genetically heterogeneous and grouped as serotypes, and the…”
Section: Introductionmentioning
confidence: 99%